Effects of inhalation of oil-paint fumes of construction industry on serum level of FSH, LH, estradiol and 17-alpha- hydroxyprogesterone in female rats - Maryam Siavashi; Rahim Ahmadi; behrooz khakpoor (Journal of Fasa University of Medical Sciences, 2017)
Background & Objective: Studies have shown that exposure to oil paint and chemical vapor emissions is followed by physiological disorders. The aim of this study was to determine the effects of inhalation of oil-paint fumes of construction industry on serum level of FSH, LH, Estradiol and 17-Alpha- Hydroxyprogesterone in female rats.